2020
DOI: 10.1159/000509258
|View full text |Cite
|
Sign up to set email alerts
|

Relationship between Serum Uric Acid and Mortality Risk in Hemodialysis Patients: A Multicenter Prospective Cohort Study

Abstract: <b><i>Background:</i></b> Several studies have reported that low serum uric acid (SUA) levels are related to increased risk of mortality in maintenance hemodialysis (MHD) patients. However, the possible detrimental effects of high SUA on the mortality risk have not been well examined. Moreover, the possible effect modifiers for the SUA-mortality association have not been fully investigated. To address the aforementioned gap, we aimed to explore the nonlinear relationship between SUA lev… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
5
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 48 publications
(42 reference statements)
1
5
0
2
Order By: Relevance
“…This U-shaped association was confirmed in both sexes; the inflection point for serum uric acid was 4 mg/dl (238 μmol/l) in women and 6 mg/dl (357 μmol/l) in men [27]. A similar U-shaped association of serum uric acid with all-cause and CVD mortality has recently been reported in other general population cohorts [28,29 ▪ ,30 ▪ ,31], the elderly [32,33], patients with type 2 diabetes mellitus [34] and patients with chronic kidney disease undergoing haemodialysis [35–37].…”
Section: Uric Acid and Cardiovascular Mortalitysupporting
confidence: 74%
“…This U-shaped association was confirmed in both sexes; the inflection point for serum uric acid was 4 mg/dl (238 μmol/l) in women and 6 mg/dl (357 μmol/l) in men [27]. A similar U-shaped association of serum uric acid with all-cause and CVD mortality has recently been reported in other general population cohorts [28,29 ▪ ,30 ▪ ,31], the elderly [32,33], patients with type 2 diabetes mellitus [34] and patients with chronic kidney disease undergoing haemodialysis [35–37].…”
Section: Uric Acid and Cardiovascular Mortalitysupporting
confidence: 74%
“…A large cohort study in Japan showed that uric acid levels may have a U-shaped association with all-cause mortality among the general population, which means that both low and high uric acid levels may increase mortality [31]. Consistently, a multicenter prospective cohort study in Chinese hemodialysis patients also certi ed a U-shaped pattern between serum uric acid level and all-cause mortality, cardiovascular disease (CVD) mortality and non-CVD mortality [32].…”
Section: Discussionmentioning
confidence: 82%
“…A large cohort study in Japan showed that uric acid levels may have a U-shaped association with all-cause mortality among the general population, which means that both low and high uric acid levels may increase mortality [ 36 ]. Consistently, a multicenter prospective cohort study in Chinese hemodialysis patients also certified a U-shaped pattern between serum uric acid level and all-cause mortality, cardiovascular disease (CVD) mortality and non-CVD mortality [ 37 ].…”
Section: Discussionmentioning
confidence: 87%